Reduced neural differentiation of rewards and punishment during passive avoidance learning in adolescents with generalized anxiety disorder. Issue 8 (19th March 2021) - Bashford‐Largo, Johannah; Aloi, Joseph; Zhang, Ru; Bajaj, Sahil; Carollo, Erin; Elowsky, Jaimie; Schwartz, Amanda; Dobbertin, Matthew; Blair, Robert James R.; Blair, Karina S.
Abstract: Background: It has been proposed that individuals with generalized anxiety disorder (GAD) show dysfunctional computations related to approach‐avoidance decision‐making. However, few studies have examined the neural basis of this impairment, particularly in adolescents with GAD. The goal of the current study was to address this gap in the literature. Method: The study involved 51 adolescents with GAD and 51 typically developing (TD) comparison individuals matched on age (16.10 and 15.75 respective means), gender (30 F/21 M and 24 F/27 M), and IQ (103.20 and 103.18 respective means). Participants underwent functional magnetic resonance imaging during a passive avoidance task. Results: We found a significant Group‐by‐Reinforcement interaction within reward‐related brain regions including the caudate, putamen, mid cingulate/paracentral lobule, and superior and middle frontal gyrus. TD adolescents showed a greater differential response to reward versus punishment feedback within these regions relative to adolescents with GAD. In particular, this reflected reduced responses to rewards in the adolescents with GAD. There were no group differences in neural responses when making approach/avoidance responses. Conclusion: The results of this study suggest reduced differential responsiveness to reinforcement as a component of the pathophysiology seen in adolescents with GAD. This dysfunction likely underpins decision‐making impairments that may exacerbate the participants' worry.